THE INFLUENCE OF ONLINE LEARNING APPLICATION WITH HIWAR METHOD AND ASSIGNMENT ON STUDENT’S MOTIVATION TO LEARNING ISLAMIC SUBJECT AT SENIOR HIGH SCHOOL, SOPPENG, SOUTH SULAWESI - Nur Ilham Asnawi; Muhammad Yaumi; Muzakkir Muzakkir (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This article discusses the influence of the application of online learning with the presentation system of the hiwar method and the assignment method on interest in Islamic education subject (PAI) learning at Senior High School (SMAN) 5 Soppeng. The type of research this research is ex-post facto. Ex-post facto research is research in which the independent variables have been treated, or treatment was not carried out at the time of the research. In this research, the data generated is not in the form of numbers, but data that is expressed symbolically in the form of words. The learning methods that have been offered by the government, are not fully heeded by students. The reason is that many of them feel bored and tired due to the many tasks given by educators. The lesson schedule takes place like classroom learning, but learning is carried out at home so that if there are four subjects in a day, then they will get four assignments at once. To overcome this, it is necessary to have an interest in learning from students.